Pengaruh Konten Makeup di Instagram terhadap Keputusan Pembelian Jasa Makeup Artist - Khaliza Maryam Zukhaer; Jenny Sista Siergar; Dwi Atmanto (Journal on Education, 2025)
Content is something that can help viewers in finding information about products or services that can be seen through social media. Instagram social media is the second most used social media application in Indonesia. Instagram is often used for business, which is used to promote products or services that are sold so that they can be better known by many people, by uploading photo or video content that promotes the results of the product or service being sold. The Instagram application is also often used by makeup artist service sellers to upload makeup content on Instagram as a promotional medium. This study aims to determine the effect of makeup content on Instagram on purchasing decisions for makeup artist services. Using an associative quantitative approach with a survey, data was collected from 99 respondents through a questionnaire that included 19 statements about makeup content and 18 statements about purchasing decisions. The results of the simple linear regression test showed a significance value of 0.000 (<0.05) and a t_count of 8.854 (>1.98472), indicating a significant influence of 44.7% between makeup content on Instagram and the purchase decision of makeup artist services.